A Manual of Dynamic Play Therapy : Helping Things Fall Apart, the Paradox of Play. - McCarthy, Dennis (Jessica Kingsley Publishers, 2012)
Children experience growth and change throughout their lives. This book explains how this reorganising process can be used in play therapy to help children dealing with social, neurological, developmental, Â health and family issues. Theory and examples are used to show how to apply the practice with a range of clients.